Extração de quitosana a partir de resíduo de camarão e seu efeito sobre leveduras do bioetanol - Tanganini, Isabella Carvalho (Universidade Federal de São Carlos, 2019)
Chitosan is a biopolymer widely used in agriculture and in the food, medical and pharmaceutical industries. It is obtained by the deacetylation of chitin, extracted from the carapace of crustaceans or fungal mycelia. Despite its potential as an antimicrobial agent, chitosan is still not used in the bioethanol industry to control process contaminant yeasts. Dekkera bruxellensis is an opportunistic yeast of great interest to the wine industry and fermentation processes for ethanol production in Brazil, and its control becomes necessary. In this context, the objective of this work was to obtain chitosan from shrimp residues by bacterial fermentation and subsequent chemical deacetylation and to evaluate its inhibitory effect on yeasts from bioethanol production. The bacterial fermentation was carried out in optimized concentrations of residue, inoculum and glucose aiming at higher production of acids. The chitin deacetylation process to obtain chitosan was done by the autoclave method, at 121 oC and 1 atm, using 45% sodium hydroxide. Chitin and chitosan obtained were characterized by infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential thermal analysis (TG-DTA) and differential scanning calorimetry (DSC). The effect of the obtained chitosan (natural) and a commercial chitosan on the growth of D. bruxellensis and an industrial strain of Saccharomyces cerevisiae (PE-2) was evaluated in sugar cane broth and YPD culture medium. The effect of adding 500 mg/L of natural chitosan to the fermentation in sugar cane broth in co-cultivation with D. bruxellensis was also evaluated. In the chitin extraction by lactic fermentation step, the conditions of higher acid production were 10% (v/v) inoculum of L. plantarum and 100 g / L of glucose. At the concentration of 5% (m/v) residue, the best results were obtained in the fermentation to obtain chitin, producing 23.09 g of lactic acid / 100 mL. The demineralization rate was 77% and deproteinization was 43%. Infrared spectra (FTIR) confirmed the presence of chitin and chitosan in the samples after fermentation and after deacetylation respectively, with 80% deacetylation degree. X-ray diffractograms showed the crystallinity profile of the samples, with chitin being more crystalline. Thermogravimetric analysis showed higher thermal stability of natural chitosan compared to commercial chitosan. Both commercial chitosan and natural chitosan reduced the maximum specific growth rate (μmax) of both yeasts and caused an increase in the lag phase of D. bruxellensis in 6 and 3.5 hours, respectively, at the concentration of 500 mg / L. The same was not observed in S. cerevisiae. This concentration of natural chitosan when added to the fermentation reduced the number of D. bruxellensis in approximately 1 log cycle after 12 hours, with minor effect in S. cerevisiae population. The fermentative efficiency was 22% higher when compared to the fermentation without chitosan. The natural chitosan obtained under the conditions of this work presents as potential antimicrobial to be used in the fermentation for the production of ethanol fuel to control the contaminating yeast D. bruxellensis, without interference in the process.
Extraction of chitosan from shrimp waste and its effect on bioethanol yeasts
Keywords: Sustentabilidade; Fermentação lática; Quitosana; Resíduo; Bioprocesso; Sustainability; Lactic fermentation; Chitosan; Residue; Bioprocess; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO